Multi-focal transmit-array designs to boost the scanning performance of small phased arrays - A F Vaquero; Matos, S.; M. Arrebola; Felício, J.; M. R. Pino; Fernandes, C. A. (43rd Antenna Workshop Antenna Technologies, 2025)
This work proposes a hybrid Phased array (PA) – transmit-array (TA) architecture that attains agile, fully electronic beam steering while preserving the high directivity of low-profile TA terminals. The core contribution is a two-stage synthesis, firstly, adapting the multi-focal TA design to account for the PA illumination, and second, proposing a regularized inversion that computes complex PA excitations which best reproduce the target quasi-Gaussian aperture illumination used in the TA design. The combined design reduces scanning aberrations and improves pointing control compared to unoptimized feeding, even when using a compact 10 × 10 PA feeder. Numerical experiments validate the approach by comparing PA far-field, and the hybrid PA-TA architecture, resulting in promising radiation patterns across a wide scanning range.